La presse féminine italienne de l’entre-deux-guerres : une question d’opinion (1922 – 1937) - Gagné-Lebel, Andréanne (Université de Montréal, 2022)
This master’s thesis analyses Italian women discourses on their living conditions in the feminine press during the fascist era, from 1922 to 1937. On the basis of three publications, l’Almanacco della donna italiana, La Donna Italiana: rivista mensile di lettere, scienze, arti e movimento sociale femminile and Il Giornale della donna, which will become, in 1935, La Donna Fascista, this study tries to demonstrate that maternity, employment and leisure are all present in the discourses, and that they have been written about openly. It is possible to note an evolution of the feminine points of view with the different events happening at the time, like Matteotti’s assassination and the new work legislation. Journalists share their ideas with multiple techniques. They use the parameters of the fascist regime to justify the role and services to which they pretend, as well as the gendered society division to self-assign some tasks and the ideals carried by the ideology to justify points of view. Therefore, despite freedom of expression restrictions during Benito Mussolini’s regime, women do have some latitude in the discourses related to their living condition, which have the particularity of being written strictly for a female audience. This thesis demonstrates the particularities of women’s discourses in a totalitarian society. To do so, the publication selection has been studied by statistical analysis first to seek out common subjects and journalists, and then by comparative analysis to demonstrate similarities and differences in the topics’ treatment.
Keywords: Emploi; Employment; Entre-deux-guerres; European history / Histoire de l’Europe (UMI : 0335); Fascism; Fascisme; Feminism; Femmes; Féminisme; Gender; Genre; Hobbies; Interwar; Italie; Italy; Journalism; Journalisme; Loisirs; Maternity; Maternité; Women